Elaboration and electrical characterization of electrodes made with Azadirachta indica’s biochar and coconut shells’ bio-pitch doped with TiO2 - ATTAH, N’Gissa; MANI, Damgou KONGNINE; MOUZOU, Essowè; KPELOU, Pali (Edelweiss Applied Science and Technology, 2025)
Composite electrodes based on carbon material have recently experienced the widest application in Plant Microbial Fuel Cells, owing to the advantageous properties that they possess. In general, the manufacturing process of these electrodes involves a complex procedure requiring high temperatures as well as the use of chemical solutions and fossil pitch as binders. This study aims to elaborate on cheap composite electrodes from neem charcoal used as an alternative carbon source and coconut shell bio-pitch used as an alternative binder to fossil coal tar. To enhance their electrical properties, a Biochar/TiO2 weight ratio of 0%, 20%, 33%, and 83% was developed. A homemade carbonizer with a lid suitable for collecting bio-oil and an electrode mold were designed and used in this study. Electrochemical impedance spectroscopy (EIS) technique was used to determine the electrical equivalent circuit of each sample, and the result was compared to the graphite recovered from a new Leclanché battery. The resistivity assessment revealed that the sample with 33% TiO2 has the lowest electrical resistivity (4.28 x 10-4 Ω.m) but is 9.3 times higher than that of graphite. The electrolytic resistivities of this sample are 1.37 Ω.cm2, compared with 1.602 Ω.cm2 for graphite. The charge transfer resistance obtained from the EIS measurements showed an electricity recovery capacity of samples containing 33% and 83% by weight of TiO2 is respectively 3.3 times and 59.8 times higher than that of graphite. This suggests that using biochar instead of fossil coal and repurposing coconut shells into bio-pitch instead of fossil pitch is a more sustainable and effective approach for producing high-performance electrodes.